La racialidad en la música: De Nicolás Guillén al rap y a Tony Ávila - Burunate Sánchez, Teresa Victoria (Comparative Cultural Studies: European and Latin American Perspectives, 2020)
The acknowledge of existence of racial discriminatory manifestations in Cuban society nowadays beside the declaration of the United Nations declaration of the decade of afro descendants in 2015 create the proper framework for developing any investigation related with racial topic. That’s why the goal of the present paper is to reveal how racial problem has been developed in Cuban music through the lyric of Nicolas Guillen’s poems Motivos de Son, the Cuban rap ¿Quién tiro la tiza? And Cientificamente Negro of Tony Avila. Originally Guillen’s poems were not conceived to be used by any musician. Nevertheless, outstanding musicians took them inspired by poems’ metric, rhythm and their poetic structure. Indeed, author main purpose was that negro people recognize and assume himself as such; the theme of the rap is a critical answer to the rebirth of hidden form of racial discrimination that emerged due to the economical social changes resulting from economical political situation while in Tony Avila’s work the negro not only conscientious assume himself as such, at the same time censure the persistence of stereotypes and exclusion racial manifestation.